2009
DOI: 10.1111/j.1365-2834.2009.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of a succession planning programme in nursing, in Australia

Abstract: Nurse Managers are in key positions to develop effective succession planning models. This study offers a process for managers to develop effective succession planning programmes within their organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…The term succession planning, familiar in management, is arguably overlooked within nursing and midwifery in many organizations. Brunero et al. (2009) highlighted the need for succession planning within nursing to be more formally operationalized.…”
Section: Introductionmentioning
confidence: 99%
“…The term succession planning, familiar in management, is arguably overlooked within nursing and midwifery in many organizations. Brunero et al. (2009) highlighted the need for succession planning within nursing to be more formally operationalized.…”
Section: Introductionmentioning
confidence: 99%
“…These programs give nurses an opportunity to both gain leadership knowledge and also make an informed decision about whether the nurse manager role is a good fit for them. 15,16 Larger organizations often open their emerging leader classes to other disciplines and departments. 17 More frequently, development efforts focus 20 NURSING ADMINISTRATION QUARTERLY/JANUARY-MARCH 2013 on those already in nursing management roles.…”
Section: Emerging Nurse Leader Developmentmentioning
confidence: 99%
“…A number of scholars provided descriptions of succession planning programmes directed toward the development and retention of nurse leaders, beginning with staff nurses and ending with chief nursing officers (CNOs). Brunero et al. (2009) reported the results of a succession planning pilot study conducted in a teaching hospital in Sydney, Australia.…”
Section: Analysis and Critique Of The Literaturementioning
confidence: 99%
“…The succession planning pilot study reported by Brunero et al. (2009) was conducted in 2006 to develop and evaluate a nursing succession planning programme at a 550‐bed metropolitan tertiary referral teaching hospital in Australia.…”
Section: Analysis and Critique Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation